The impact of various trade arrangements on Malaysia’s bilateral trade costs - Tan, Jiunn Woei; Lee, Chin; M. Azali,; Normaz Wana Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The benefits of trade agreements on trade activities are notably acknowledged but the impact on bilateral trade costs remains obscure and have to be further examined. First, this study will construct the micro measure of bilateral trade cost, and then the constructed trade costs will be utilized to estimate the impact of trade arrangements on trade costs for Malaysia and her trading partners for the year 2002-2012. The results show that all four types of trade arrangements, namely the Multilateral Trade Arrangement (MTA), Regional Trade Arrangement (RT A), Bilateral Free Trade Arrangement (BFTA) and Bilateral Trade Arrangement (BT A) have lowered trade costs. In addition, the different types of trade arrangements result in a variation of trade costs, where regional trade arrangements are expected to reduce bilateral trade costs the most. However empirical result shows otherwise where BFTA gave the highest reduction in trade costs for Malaysia. As to date, the number of BFTA that has been signed is far behind BT A. It is recommended that Malaysia realign its focus towards BFTA with the hope that Malaysia and her trading partners will experience a greater reduction of trade costs in the coming years.